Problematika Pengawasan Dewan Pengawas Syariah Pada BMT Almaun Berkah Madani dan BMT Mandiri Ukhuwah Persada - Fathin Su'aidi; Irham Zaki (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
Sharia Board is an commite in sharia financial institution and assigned overseeing the implementation of the decisions of the National Sharia Board (DSN) in Islamic financial institutions. Sharia Board functions to supervise sharia compliance in sharia financial institutions including the Baitul Maal Waat Tamwil (BMT). BMT is a sharia micro finance institution that combines the concept of maal and tamwil . This study aims to determine the problems faced by the Sharia Board in conducting supervision in BMT. The point that is necessary reviewed in this supervisory practice are based on Decree MUI DSN No. 3 of 2000 concerning instructions for implementing the determination of members of the sharia board in sharia financial institutions. This study use qualitative methods with descriptive case study strategy. From the results of the research occur several problems were encountered by the Sharia Board including: lack of the professionalism of Sharia Board, lack of commitment, lack of independence, and challange to mobilize all elemnts os sharia financial institution to comply with sharia law.The sloution of the problematic is by upgrade an increase faith and taqwa ang commitment to enforce sharia especially as the Sharia Board. always implementing the principles of Good Corporate Governance, and the governmemt making strong and clear rules of sharia supervisions.Keywords: Problematic , Sharia Board , Baitul Maal Wat Tamwil